2023
DOI: 10.1007/s10055-023-00817-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of digital literacy in augmented, virtual, and mixed reality in popular science education: a review study and an educational framework development

Abstract: This study aims to bridge the gap between extended reality (XR) and digital literacy (DL) in popular science education and further develop a DL–XR framework. XR includes augmented, virtual, and mixed reality (AR, VR, and MR), which has received increased attention and has been used for educational purposes in recent years. However, the studies of XR in popular science education and its impact on students are scant. It is also challenging to find studies entailing XR and DL in education. This study not only off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The VOS Viewer offers bibliometric analysis mapping with three different visualizations, including the overlay visualization mentioned (see Figure 12). Based on Figure 12, Augmented Reality research is more related to clinical articles (Jeffers et al, 2022;Lau et al, 2023), extended reality (Chang et al, 2023;Gurses et al, 2023;Spadoni et al, 2022), likert scale (Soyka & Simons, 2022;Zatarain-Cabada et al, 2023), and nuclear magnetic resonance imaging (De Benedictis et al, 2023;Shahbaz et al, 2023). Additionally, Augmented Reality research is applied from early childhood education to higher education levels (Senduk et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The VOS Viewer offers bibliometric analysis mapping with three different visualizations, including the overlay visualization mentioned (see Figure 12). Based on Figure 12, Augmented Reality research is more related to clinical articles (Jeffers et al, 2022;Lau et al, 2023), extended reality (Chang et al, 2023;Gurses et al, 2023;Spadoni et al, 2022), likert scale (Soyka & Simons, 2022;Zatarain-Cabada et al, 2023), and nuclear magnetic resonance imaging (De Benedictis et al, 2023;Shahbaz et al, 2023). Additionally, Augmented Reality research is applied from early childhood education to higher education levels (Senduk et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…By combining traditional teaching methods with digital tools, educators can encourage a blended learning approach that increases engagement and retention [22]. The use of digital resources also enables personalized learning experiences, allowing students to explore scientific concepts at their own pace and according to their individual interests [23]. The interactive and multimedia nature of digital resources can contribute to a deeper understanding of scientific principles [24].…”
Section: Integration Of Science Teaching Methods and Digital Literacymentioning
confidence: 99%
“…Research across contexts, including college sports, professional coaches and event management staff, has shown that human capital investments are related to improved career outcomes DEI in the sport metaverse (Breuer et al, 2022;Kaplanidou et al, 2021;Weight et al, 2021). Digital literacy is one source of human capital that is vital in the new economy (Chang et al, 2023). Experience and immersion in the sport metaverse has the potential to increase people's digital literacy, thereby increasing their career prospects.…”
Section: Opportunitiesmentioning
confidence: 99%